A study on the characteristics of palm-based polyurethane as a lightweight aggregate in concrete mix - Kamarul Aini Mohd Sari; Sohif Mat; Khairiah Haji Badri; Muhammad Fauzi Mohd Zain (Universiti Kebangsaan Malaysia, 2015)
Research on the development of lightweight concrete (LWC) utilizing wastes and natural resources as lightweight aggregates (LWA) is increasingly gaining attention worldwide due to sustainable and environmental concerns. A new alternative is using palm kernel oil polyol (PKO-p)-based polyurethane (PU) as filler. Rigid PU is a block copolymer comprised of a monomeric PKO-p and 2, 4-methylene diphenyl diisocyanate (crude MDI). The property of PKO-p, its ratio with crude MDI and reaction time were determined. The reaction time showed the average of 60 s for cream time and 95 s for rise time with maximum hardening time of 8 min. The reaction between PKO-p to MDI at 1:1 ratio resulted in a very short hardening time (within 2 min). The compressive strength of the rigid PU was at 7.0 MPa at a density of 206 kg/m3. Further increase in the amount of PKO-p increased the density and compressive strength of the PU. PU aggregate in the concrete mixture was added at 1 to 5% (w/w) to obtain concrete with density of less than 1800 kg/m3. The resulting concrete has excellent compressive strength (17.5 MPa) and thermal conductivity (0.24 W/m⋅K). The results showed that physical properties of PU played the most significant effect on the physical and mechanical properties of the lightweight concrete.